Pemikiran Tokoh Pendidikan dalam Buku Lifelong Learning: Policies, Practices, and Programs (Perspektif Peningkatan Mutu Pendidikan di Indonesia) - I Ketut Sudarsana (UHN IGB Sugriwa Denpasar, 2016)
The substances of the views of the some figures depicted in the Lifelong Learning Policies, Practices, And Programs, especially the ones found on Chapter 11 to 15 mostly describe the relation between the school education, families, and society. They are in accordance with the Indonesian Government Regulation No20/2003 on the national system of Indonesian education that regulate its informal, formal and nonformal sectors. The least attended nonformal one has actually equal charge, namely providing the best education to the society.